Efektivitas Media Edukasi Gizi Terhadap Upaya Pencegahan Stunting : Literature Review - Syarfaini, Syarfaini; Tahar, Titah Nurul Latifah; Hadza, Roza Qoni; Sumarlin, Rudi; Nurfadillah, Annisa; Irvan, Muh; Husain, Zulfa; Kanang, Bau (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2024)
Nutritional knowledge is an important factor that influences the nutritional behavior of individuals, families, and communities. Providing nutrition and health education media to parents is one of the efforts that can be made to improve children's growth and development. The purpose of this study was to determine the effectiveness of nutrition education media on stunting prevention efforts. This study uses the literature review approach method which contains reviews, summaries, and author's thoughts from several literature sources on the topic discussed. After screening from 471 articles, 24 relevant articles were obtained that have similarities with the topic of this research. Some of the educational media reviewed are posters, booklets, leaflets, comics, pocket books, and flipcharts. Of all the studies reviewed, it is known that booklet media has proven effective in increasing public knowledge related to stunting.